EXOTICISM "KALA" IN TRADITIONAL MOTIF ON WOOD AND METAL MEDIA - Prabowo, Rahayu Adi (Acintya, 2024)
Kala is one of the decorative motifs or ornaments carved on temples in Indonesia. Kala is in the shape of a giant head or face which is an imaginary ornament or imaginary motif which is a form of art from past cultures. The appearance of the kala motif usually does not refer to fragments of the storyline, but rather to a form of display that symbolizes protection and honor. The development of the form of the kala motif has been widely carried out as an act of cultural preservation which has the aim of expanding the meaning of the essence of the existence of the kala motif. Efforts to develop the kala motif in various forms and styles refer to deepening its aesthetic meaning, namely how its existence can be recognized and understood as a form of fine art wealth which is very important to maintain its continuity. This article about kala works is an attempt to develop the aesthetic appearance of kala forms in wood and metal media that have never been presented before. This research uses media and technique exploration methods, namely presenting works in wood and metal media using traditional carving techniques. This method provides a strong understanding of traditional artistic works with presentations that prioritize the main characters of the kala motif, namely firmness, valor, and authority.